Fenômenos de enfermagem relacionados ao termo "razões para as ações” em mulheres atendidas em um serviço de ginecologia de Fortaleza-CE - Palmeira, Isaura Letícia Tavares (2005)
The several health problems have been hiting the feminine population in the last years as, for example, the breast and uterus' câncer incidence incrcase. The nursing consultation to this population has been implcmented as contribution form for the change attempt of this profile. However, this Service has been facing difficulties by the inexistence of specific data for the nursing work. The International Classification for the Nursing Practice - ICNP is an attempt to unify world-wide for nursing language. In this study it sought to analyze the nursing phenomena described in ICNP - Alpha version that composes the item “Reasons for Actions” in women attended in 219 women who were attended in a Basic Unit of Family Health with resident women in the Fortaleza city in the period of January to March of 2004. They were found 35 nursing phenomena that indicate health maintenance (12) and that indicate health alteration (23). From the First, three were below P?5, being considered for the most profound analysis, because, rcprescnt a gap in the health condition from this women, are them present Memory in just 51,1%, Emotion, in 13,2% and Belief, in 6,4%. The phenomenon Memory showed association with lows her education and the domestic occupation (p=0,0139 e p=0.0I67). Did not exist association between the three phenomena. The Phenomena that indicate health alteration that were above of P75, they were Value Belief (84,4%), Fear (79,5%), Religious Belief (60,7%), Disorientation (48,9%) and Impotence (26%). The Religious Belief phenomena and Fear did not show association with socioeconomic factors (p>0,05). The Religious Belief showed association with low levei of scolarity and age > 40 years. The Disorientation was associated to the low levei of scolarity and to the domestic occupation and the Impotence with number reduced of family members. When Crossing the phenomena that indicated health alteration to each other, were not evidenced associations showing independence among them. It concluded that the occurrence of these phenomena happened of independent form to each other. The utilization of the International Classification for the Nursing Practice in its version Alpha presented limitations in some terms complicating the analysis of some phenomena. This work’s contribution is establish statistic dates to nursing phenomena specially to the main phenomena on gynecology area.